2017
DOI: 10.1002/mrd.22852
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin regulates the speed of oviductal fluid flow in cattle

Abstract: Unidirectional flow of oviductal fluid from the ovarian to uterine side of the ampulla plays a significant role in successful pregnancy, and is produced by ciliary beating. Various systems regulate ciliary beating, such as paracrine, autocrine, and endocrine. We hypothesized that Adrenomedullin (ADM)-a peptide hormone that acts via its receptors, which are complexes of Calcitonin receptor-like receptor (CRLR) and Receptor activity-modifying protein (RAMP) 2 or 3 - promotes oviductal fluid flow in the ampulla o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, to date, there are no data on the effect of COD on ciliary beating, which contributes to tubal fluid flow and PTS (Niwa et al, 2012;Noreikat et al, 2012). Previous research has shown that PTS in the oviduct is affected by lipopolysaccharide (O'Doherty et al, 2016) and adrenomedullin (Yoshimoto et al, 2017).…”
mentioning
confidence: 99%
“…However, to date, there are no data on the effect of COD on ciliary beating, which contributes to tubal fluid flow and PTS (Niwa et al, 2012;Noreikat et al, 2012). Previous research has shown that PTS in the oviduct is affected by lipopolysaccharide (O'Doherty et al, 2016) and adrenomedullin (Yoshimoto et al, 2017).…”
mentioning
confidence: 99%